Motivations for improvements between elite professional athletes playing in Europe: A quantitative study - Moss, D'. (ProQuest Dissertations Publishing, 2020)
Societal views on women`s bodies and muscularity over the course of modern time have come a long way from traditional thin ideals. While many college athletes proclaim a sense of motivation to gain muscularity for their sport, little is known in the professional circuit. The purpose of this study was to investigate the ages and nationalities of professional women basketball players in Europe to determine the main effects and interactions on drives for muscularity and sport motivation. Current research explores drives for muscularity on college samples, negating the need to study professional samples of women professional players in markets outside of the United States. Utilizing a snowball sampling method, participants were recruited on the basis of the relationship to the researcher with additional help from Whatsapp Messenger and Instagram social media services. McCreary and Sasse's (2000) 15-item Drive for Muscularity Scale (DMS) and the 24-item Sport Motivation Scale (SMS-6), a 2007 instrument by Mallet, Kawabata, Newcombe, and Otero-Forero were used to survey the 99 total participants (N = 99). The sample consisted of participants from 19 different countries and nationalities. A factorial univariate analysis of variance (ANOVA) was used to analyze the data with SPSS statistical software. The results indicated that the main effects of nationality on DMS average scores and RAI scores produced significant differences, while the interactions of nationality and age on DMS and RAI scores, as well as main effects of age on DMS and RAI scores did not produce significant differences.